Integrasi Pasar Berjangka Komoditi Crude Palm Oil (CPO) Indonesia Di Masa Pandemi Covid-19 - Octaviana Helbawanti; Cici Aulia Permata Bunda; Faqihuddin Faqihuddin (Jurnal Agrica, 2022)
Crude Palm Oil (CPO) commodity trading has been carried out domestically and exported, so that the price developments formed are domestic trading prices in the spot market and global prices in international market level. Price fluctuations in CPO agriculture increased the risk of trade causing uncertainty in the spot market and derivatives market. Price uncertainty was the impact of the inability of a market to follow the price changes in other markets. Research on CPO prices in the derivatives market and spot market was aimed to analyze market cointegration and causality. Johansen Cointegration Test and the Granger Causality Test were applied to this research. The Johansen Cointegration test results explained that the derivatives market and the spot market of Crude Palm Oil (CPO) were not long-term cointegrated. The Indonesian CPO market has not been able to become an international reference market due to derivative transactions and lack of literacy. The spot market that was unable to follow the movements of the derivatives market might be caused by price fluctuations due to uncertainty during the Covid-19 pandemic with social restrictions on global trade activities. There was one-way causality from the analysis using Granger Causality. The causality test depicted the derivatives market affected the spot market, so that changes or shocks in the derivatives market could be transmited into spot market. The derivatives market at the global level heading to Rotterdam as a market leader showed price discovery function, while the Indonesian spot market became market follower. The demand of CPO in the European market was high for biofuels and many industral purposes and there were regulations on the use of CPO which have contributed to the influence of the spot market in Indonesia. The derivative market provided future price information intended minimize the uncertainty of price changes.